Effect of a multimodal non-pharmacological intervention on older people with dementia: a single-case experimental design study - Kyosuke Yorozuya; Yoshihito Tsubouchi; Yuta Kubo; Yoshihiro Asaoka; Hiroyuki Hayashi; Takashi Fujita; Hideaki Hanaoka (BMC Geriatrics, 2022)
Abstract Background Older people with dementia (PWD) in nursing homes (NHs) tend to have decreased cognitive function, which may cause behavioral and psychological symptoms of dementia (BPSDs) and hinder activities of daily living (ADLs). Therefore, taking measures against the cognitive decline of PWD in NH and, in turn, the decline of BPSDs and ADLs is crucial. The purpose of this study was to test whether a multimodal non-pharmacological intervention (MNPI) is effective in maintaining and improving global cognitive function, BPSDs, and ADLs in PWD in NHs. Methods An intervention study using a single-case AB design was conducted in three subjects in NHs. During the non-intervention phase, participants underwent follow-up assessments, and during the intervention phase, they participated in an MNPI. The ABC Dementia Scale (which concurrently assesses ADLs [“A”], BPSDs [“B”], and cognitive function [“C”]) was used for the assessment. Results One of the three patients showed improvement in dementia severity, global cognitive function, ADLs, and BPSDs. However, the other two participants showed no improvement following the MNPI, although the possibility of a maintenance effect remained. Conclusion Although there is room for improvement of the MNPI, it may be effective in maintaining and improving cognitive function, ADLs, and BPSD, in PWD in NHs. Trial registration The University Hospital Medical Information Network Clinical Trials Registry ( http://www.umin.ac.jp/ , No. UMIN000045858, registration date: November 1, 2021).